Exploring the determinants on continuance participation of college students toward blended learning: the stimulating role of course characteristics and instructor support - She, Maoyan; Xu, Yiyang; Li, Zhigang; Hu, Die (Frontiers in Psychology, 2025)
BackgroundBlended learning (BL) has become an important learning method in the high education with the rapid advancement of “Internet + Education,” however, college students face notable challenges, such as high dropout rates, low participation and low persistence, which largely reduce the learning effect of BL. Therefore, it is necessary to deeply analyze the question: “What factors will influence college students’ continuance behavior in blended learning (CBBL)?”MethodsBased on the stimulus-organism-response (SOR) framework and social cognitive theory, this study constructs an integrated model of “Contextual facilitators–Individual characteristics–Continuance behavior,” to examine the relationships among the blended course characteristics (BCC), instructor support (IST), individual attributes, such as learning motivation (LM), self-efficacy (SEF) and learning engagement (LET), and college students’ CBBL. Colleting 466 College students who participated in BL through Chinese university MOOCs, the structural equation modeling (SEM) approach was used to test the proposed hypotheses.ResultsThe empirical results indicating that, (1) this integrated model explains 62.85% of the variance in college students’ CBBL, and LM, SEF, and LET emerge as the key determinants influencing college students’ CBBL. (2) BCC positively affects LM and LET but has no significant on SEF, and it promotes college students’ CBBL through LM and LET rather than SEF. (3) ITS exerts a significant influence on LM, SEF, and LET, with the most pronounced impact on LET. Moreover, ITS significantly facilitates college students’ CBBL via LM, SEF, and LET.Originality/valueThis study theoretically contributes to literature on BL and extends the application scope of SOR framework. Also, it reveals the antecedents of college students’ CBBL in the BL environment, which is crucial for guiding their continuance learning and promoting the sustainable development of BL education.